Ketone-selenoesters as potential anticancer and multidrug resistance modulation agents in 2D and 3D ovarian and breast cancer in vitro models - Dobiasová, Simona; Szemerédi, Nikoletta; Kučerová, Denisa; Koucká, Kamila; Václavíková, Radka; Gbelcová, Helena; Ruml, Tomáš; Domínguez-Álvarez, Enrique; Spengler, Gabriella; Viktorová, Jitka (Scientific reports, 2022)
Long-term treatment of cancer with chemotherapeutics leads to the development of resistant forms that reduce treatment options. The main associated mechanism is the overexpression of transport proteins, particularly P-glycoprotein (P-gp, ABCB1). In this study, we have tested the anticancer and multidrug resistance (MDR) modulation activity of 15 selenocompounds. Out of the tested compounds, K3, K4, and K7 achieved the highest sensitization rate in ovarian carcinoma cells (HOC/ADR) that are resistant to the action of the Adriamycin. These compounds induced oxidation stress, inhibited P-gp transport activity and altered ABC gene expression. To verify the effect of compounds, 3D cell models were used to better mimic in vivo conditions. K4 and K7 triggered the most significant ROS release. All selected selenoesters inhibited P-gp efflux in a dose-dependent manner while simultaneously altering the expression of the ABC genes, especially P-gp in paclitaxel-resistant breast carcinoma cells (MCF-7/PAX). K4, and K7 demonstrated sensitization potential in resistant ovarian spheroids. Additionally, all selected selenoesters achieved a high cytotoxic effect in 3D breast and ovarian models, which was comparable to that in 2D cultures. K7 was the only non-competitive P-gp inhibitor, and therefore appears to have considerable potential for the treatment of drug-resistant cancer.
Keywords: mnohočetná léková rezistence; nádory prsu; nádorové buněčné linie; protinádorové látky; doxorubicin; Drug Resistance, Multiple; Female; Antineoplastic Agents; Ketones; Breast Neoplasms; Doxorubicin; Cell Line, Tumor; Humans; ženské pohlaví; lidé; chemorezistence; ketony; Drug Resistance, Neoplasm